2023
DOI: 10.1002/adom.202300475
|View full text |Cite
|
Sign up to set email alerts
|

Half‐Integer Topological Charge Polarization of Quasi‐Dirac Bound States in the Continuum

Abstract: The non‐trivial polarization topology of bound states in the continuum (BICs) provides new strategies in nanophotonics. The polarization topology depends on the geometric parameters and energy‐momentum dispersion of the system and can be engineered to add specific functionalities for light molding. Herein, such a possibility is investigated by studying the topology of the polarization states associated with the optical field radiated by BICs when Dirac‐cone‐degeneracy is lifted. The opening of a pseudogap in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Thus, the nanoparticles are not only affected by p O but also by p s [14]. The optical forces applied on the nanoparticles are [38] ⟨F⟩ = δV ⟨T⟩ • n(r)dS (7) where the force and the Maxwell tensor (T see Equation ( 2)) are time-averaged and n(r) is the normal along the surface of the nanoparticle and δV is the boundary where the force is evaluated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the nanoparticles are not only affected by p O but also by p s [14]. The optical forces applied on the nanoparticles are [38] ⟨F⟩ = δV ⟨T⟩ • n(r)dS (7) where the force and the Maxwell tensor (T see Equation ( 2)) are time-averaged and n(r) is the normal along the surface of the nanoparticle and δV is the boundary where the force is evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…In nanophotonic systems, a variety of extraordinary properties and phenomena, leading to key technological innovations, descend from the coupling of photon spin angular momentum (SAM) with its spatial degrees of freedom [1,2]. Spin-orbit coupling can be observed in basic optical phenomena, such as the light propagation in anisotropic media [3][4][5][6][7], nonparaxial optics [8][9][10], and reflection/transmission at dielectric interfaces, manifesting the spin Hall effect of light [11,12]. It has been theoretically and experimentally demonstrated that electromagnetic waves also reveal a quantum spin Hall effect in analogy with the electronic effect in topological insulators [13].…”
Section: Introductionmentioning
confidence: 99%